Address to the Special Commemorative Meeting of the United Nations General Assembly on the occasion of the Fiftieth Anniversary of the United Nations - Carrington, Edwin W. (CCS GeorgetownGY, 1995)
Highlights the role played by the United Nations in the development of small nations states like Caricom. Notes the efforts of Caricom in regional integration. Congratulates the United Nations on the occasion of its 50th anniversary.